1998
DOI: 10.1016/s1078-5884(98)80202-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological evidence that neovascularisation is a cause of recurrent varicose veins

Abstract: Neovascularisation was the principal cause of recurrent saphenofemoral incompetence in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
103
1
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 18 publications
4
103
1
13
Order By: Relevance
“…11 In 70% of cases, this has been due to groin neovascularisation, secondary to angiogenesis of the postoperative reparation following groin dissection. 11,12 Recurrence rates at two years in endovenous ablation remain under 7% at present. 13 Untreated refluxing tributaries (accessory saphenous vein or duplex saphenous system) and refluxing perforators increase the risk of recurrence but are uncommon (<5%).…”
Section: Discussionmentioning
confidence: 97%
“…11 In 70% of cases, this has been due to groin neovascularisation, secondary to angiogenesis of the postoperative reparation following groin dissection. 11,12 Recurrence rates at two years in endovenous ablation remain under 7% at present. 13 Untreated refluxing tributaries (accessory saphenous vein or duplex saphenous system) and refluxing perforators increase the risk of recurrence but are uncommon (<5%).…”
Section: Discussionmentioning
confidence: 97%
“…Recurrence was previously thought to be caused by poor surgical technique, especially when operations were performed by surgical trainees 99 , anatomical variability and complexity of the saphenofemoral junction 100 , and disease progression 101 . However, it is now believed that neovascularization reconnecting the venous channels is the probable cause of most recurrent disease 102,103 .…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularization is thought to be the result of angiogenesis following the tissue trauma of surgical dissection 29 , whereas it is speculated that extravenous inflammation does not occur following EVLA. It has been suggested that the preservation of groin tributaries during EVLA avoids the stimulus for angiogenesis 40 ; some surgeons even preserve groin tributaries during saphenofemoral ligation on this basis 41 .…”
Section: Discussionmentioning
confidence: 99%